Poultry Manure as a Fertilizer - Michael A. Davis; Doug R. Sloan; Gerald Kidder; R. D. Jacobs (EDIS)
Animal manures have been used as natural crop fertilizers for centuries. Because of poultry manure’s high nitrogen content, it has long been recognized as one of the most desirable manures. Besides fertilizing crops, manures also supply other essential plant nutrients and serve as a soil amendment by adding organic matter, which helps improve the soil’s moisture and nutrient retention. Organic matter persistence will vary with temperature, drainage, rainfall, and other environmental factors. This 2-page fact sheet was written by Michael A. Davis, D.R. Sloan, Gerald Kidder, and R.D. Jacobs, and published by the UF Department of Animal Science, November 2013. http://edis.ifas.ufl.edu/aa205